'The tunnel road is not the road to peace'. Protest against exclusion of Arabs from "the tunnel road" in West Bank, south of Jerusalem. Drawing on plastic cardboard
'The tunnel road is not the road to peace'. Protest against exclusion of Arabs from "the tunnel road" in West Bank, south of Jerusalem. Drawing on plastic cardboard.